2017
DOI: 10.1038/pr.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency in neonatal hypoxic–ischemic encephalopathy

Abstract: BackgroundVitamin D has neuroprotective and immunomodulatory properties, and deficiency is associated with worse stroke outcomes. Little is known about effects of hypoxia-ischemia or hypothermia treatment on vitamin D status in neonates with hypoxic-ischemic encephalopathy (HIE). We hypothesized vitamin D metabolism would be dysregulated in neonatal HIE altering specific cytokines involved in Th17 activation, which might be mitigated by hypothermia.MethodsWe analyzed short term relationships between 25(OH) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 43 publications
6
25
1
Order By: Relevance
“…[6][7][8] Recent studies have demonstrated that the majority of infants who have suffered from HIE have vitamin D deficiency. 9 The resulting neuronal injury in HIE is primarily driven by hypoxia and inflammation, and vitamin D appears to be protective against both. 10 Vitamin D reduces differentiation and proliferation of lymphocytes that produce the proinflammatory cytokine interleukin (IL)-17, 11,12 and vitamin D insufficiency is associated with low levels of the anti-inflammatory cytokines IL-10, IL-17E (IL-25), and IL-27.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Recent studies have demonstrated that the majority of infants who have suffered from HIE have vitamin D deficiency. 9 The resulting neuronal injury in HIE is primarily driven by hypoxia and inflammation, and vitamin D appears to be protective against both. 10 Vitamin D reduces differentiation and proliferation of lymphocytes that produce the proinflammatory cytokine interleukin (IL)-17, 11,12 and vitamin D insufficiency is associated with low levels of the anti-inflammatory cytokines IL-10, IL-17E (IL-25), and IL-27.…”
Section: Introductionmentioning
confidence: 99%
“…10 Vitamin D reduces differentiation and proliferation of lymphocytes that produce the proinflammatory cytokine interleukin (IL)-17, 11,12 and vitamin D insufficiency is associated with low levels of the anti-inflammatory cytokines IL-10, IL-17E (IL-25), and IL-27. 9,[11][12][13] As such, insufficient levels of 25-hydroxyvitamin D (25OHD) could be an aggravating factor after neonatal HIE; however, there is minimal published data assessing the effects of vitamin D levels on outcomes in human neonates with HIE. 9 Although vitamin D deficiency has been associated with HIE, there has historically been considerable controversy in the literature in defining deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…31 P-MRS may provide quantitative parameters for evaluating graft viability ex vivo and is a promising tool for objective non-invasive assessment of the quality of human pancreas grafts prior to transplantation or islet isolation. Lowe, et al positively correlated [23] anti-in lammatory cytokine IL-17E with serum 25(OH) vitamin D insuf iciency present in the majority of term HIE neonates. Layec, et al assessed muscle metabolism and peripheral hemodynamics in healthy, untrained, elderly individuals subjected [24] to dynamic plantar lexion exercise and other imaging examinations including phosphorus magnetic resonance spectroscopy (31P-MRS).…”
Section: Discussionmentioning
confidence: 98%
“…In infants with HIE, both the infants and their mothers have been found to have decreased levels of vitamin D [18]. One study demonstrated that at the time of NICU admission, 70% of infants with hypoxic-ischemic brain injury were considered to be vitamin D-deficient, and many of these infants continued to have declining levels for 72 h after the injury despite the administration of parenteral nutrition containing vitamin D 2 supplementation of about 400 IU/day.…”
Section: Vitamin D and The Injured Brainmentioning
confidence: 99%
“…Given the data supporting the role of vitamin D as a protective neurohormone, investigators have begun to assess if vitamin D could play role in the prevention or therapy of neonatal HIE. Early results have demonstrated low levels of vitamin D in infants and the mothers of infants who have suffered from HIE [18], and the neonates’ serum vitamin D levels often continue to decline for 72 h after the injury despite supplementation [19]. The story of the interaction between vitamin D and neonatal HIE has just begun to unfold, and many questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%